Rectal and skin temperature of new born piglets born in two different systems - Nilsson Edenfur, Sabina (2018)
The trial was performed during the year 2015- 2016 at a farm located in the south of Sweden. The aim was to compare the drop in body temperature after birth in pigs in two different farrowing/birth systems; temporary confined sow (at farrowing until 3 days thereafter) (TC) or loose sow. The rectal and skin temperature (caudal dorsal) of 51 new born piglets was taken directly after birth and then every 15 minutes for 2 hours and 45 minutes (12 measurements). Besides rectal/skin temperature and farrowing/birth system, the following information of the individual piglet was recorded: date of birth, birth weight, if the piglet was born on concrete (with floor heating) or cast iron, amount of straw at birth place, and if the piglet was under the heating lamp at any of the 12 measuring occasions. In the TC system, the heating lamp was placed behind the sow at farrowing. This was not an option in the loose system, since the heating lamp had to be protected from the sow. Depending on birth weight, the piglets were divided into large (>1.5 kg), medium (1-1.5 kg) or small (<1 kg) piglets. In total, 21 pigs were categorized as large, 24 as medium and 6 as small. The results showed a difference between piglets with low birth weight compared to piglets with high birth weight. Piglets with low birth weight reached preferable temperature levels later than heavier piglets and low birth weight piglets also dropped more in rectal temperature. Measurements with an infra-red-thermometer of surface temperatures within the different combinations of floor type, straw and heating lamp ranged from 15°C for cast iron without lamp and without straw, 17°C for cast iron without lamp but with straw, 21°C for cast iron with lamp but without straw, 25.5°C for concrete with floor heating without lamp and straw to 27.5°C for concrete with floor heating as well as with lamp and with straw. A minor comparison between a birth place with ‘a little amount of straw’ versus a ‘lot of straw’ within medium pigs in the system with a loose sow, showed a larger temperature drop (about one degree) if the piglets were born on a little amount of straw. A similar minor comparison around being under the heating lamp or not, was made for large pigs in the TC system. This comparison did not indicate any strong results on the piglets rectal and skin temperatures due to a low number of data (only three large pigs under the heating lamp in the TC system). For large (>1.5 kg) and medium (1-1.5 kg) piglets, the body temperature drop after birth was larger in the TC system compared to in the loose system. This was explained as a consequence of that 100% of the piglets in the TC system were born on cast iron compared to only 11% in the system with a loose sow. However, for the small piglets (< 1 kg) the result was the opposite. One explanation of this contradictory result for small pigs might be that the distribution of vitality among the small piglets was uneven within the systems, since the number of small pigs was very limited (only six pigs in total). It was concluded that the skin temperatures tended to follow the rectal temperatures with a difference of about 3-6 degrees lower than the rectal temperature, and that a well-placed heating lamp, floor heating and an optimal floor are important key factors for a smaller temperature drop in newborn piglets. Straw is another positive factor for the piglets, since it makes the heat disappear slower. The lay-out of the pen was found to influence the drop in body temperature after birth. Concrete with floor heating (loose system) resulted in a better outcome compared to cast iron (TC system) in this trial in which the layout in the TC-system resulted in that the piglets were born on cast iron.